Peningkatan Kemampuan Membaca Pemahaman Dengan Teknik Skema Pada Siswa Kelas Xi Ipa-2 Sma Negeri 2 Watampone Kabupaten Bone - Marlina Saiful (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
Abstract. This study aims to improve the ability to read comprehension with scheme techniques in students class XI IPA-2, SMA Negeri 2 Watampone Bone District. The approach of this research is qualitative approach. This type of research is classroom action research. Techniques used in collecting data, namely observation, interviews, and tests. Technique of data analysis result of research done by using descriptive analysis. The results of this study indicate that the ability to read comprehension using the scheme technique in cycle I is categorized as low, while the ability to read comprehension using the scheme technique in cycle II, is categorized medium and high. This shows that there is an increase in reading comprehension skills in students of grade XI IPA-2, SMA Negeri 2 Watampone Bone District. The percentage of reading comprehension ability with scheme technique in cycle I of 35% or 14 students from 40 students are in complete category, and 65% or 26 students from 40 students are in incomplete category. While in the second cycle of 92.5% or 37 students of 40 students are in the category of completion, and 7.5% or 3 students of 40 students are in the category is not complete.